PENYULUHAN DAN PENGEMBANGAN KELOMPOK TANI SERTA PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN HASIL PRODUKSI PERTANIAN DI DESA LAMU SERTA MENCIPTAKAN DESA PEDULI LINGKUNGAN DAN TANGGAP BENCANA DI DESA AYUHULALO MENUJU DESA SEHAT DAN SEJAHTERA KECAMATAN TILAMUTA KABUPATEN BOALEMO - Rosbin Pakaya (Univeristas Negeri Gorontalo, 2022)
This program aims to increase the knowledge of students and community members on how to deal with pests that attack corn plants; Help prepare the Lamu village community, especially corn farmers to have the ability to eradicate pests and manage corn plants well by providing counseling and developing farmer groups and empowering communities to increase production output; Increased knowledge of students and community members about environmental cleanliness and healthy and prosperous villages as well as the concept of natural disaster management based on community involvement and empowerment that is resilient to disasters. The methods implemented in this activity are the methods: socialization, counseling, empowerment and discussion. This activity was carried out in Lamu Village and Ayuhulalo Village, Tilamuta District, Boalemo Regency, and was integrated with Real Work Lectures (KKN), Research and Community Service Institute (LPPM) Gorontalo State University (UNG) in 2021. This activity was directly supported by Lamu Village officials and Ayuhulalo village officials, led by the Lamu Village Head and Ayuhulalo Village Head as partners in this program.